Red blood cell distribution width: a promising index for estimating disease activity of Systemic lupus erythematosus - Abira, Mahmuda; Akhter, Qazi Shamima; Islam, Mohammad Sirajul (Journal of Bangladesh Society of Physiologist, 2022)
Background: Systemic lupus erythematosus (SLE) is a chronic inflammatory disease and is associated with considerable morbidity. Elevation in red cell distribution width (RDW), a simple routinely done investigation, could be a prognostic marker in SLE patients. Objective: To assess red blood cell distribution width for estimating disease activity in patients with SLE. Methods: This cross-sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2016 to June 2017. For this study, 30 SLE patients, aged 18 to 55 years, were considered as the study group and 30 aged matched healthy subjects were considered as control group. SLE Disease Activity Index (SLEDAI) score was used to assess disease activity. RDW and ESR were also estimated. Independent samples t-test, Chi Square test, Pearson’s correlation co-efficient (r) test, Regression analysis, Diagnostic accuracy test and ROC curve analysis were performed as applicable.. Results: In this study, RDW and ESR was significantly (p=0.000) higher in SLE patients in comparison to that of control. A significant association was observed among RDW, ESR and active disease (OR; 5.33, 95% CI; 0.78 to 36.33 and OR; 5.66, 95% CI; 0.75 to 42.36, p=0.001). RDW was positively correlated with SLEDAI score and ESR in patients with SLE. It was 84.2% sensitive and 72.7% specific for diagnosing active disease. Conclusion: This study concludes that RDW is increased in SLE patients and can be served as a useful index to estimate the disease activity. J Bngladesh Soc Physiol 2021;16(1): 95-103